Implementasi Metode Secant dalam Penyelesaian Persamaan Nonlinear Menggunakan Microsoft Excel dan Maple - Kiki Insani Sholihah; Isnaini Qoiriyah; Ari Wibowo (Griya Journal of Mathematics Education and Application, 2025)
This study aims to implement and compare the effectiveness of the secant method in solving nonlinear equations using two different computational applications microsoft excel and maple. The research adopts a descriptive qualitative approach with a comparative methodology. The secant method, which is part of numerical methods commonly used to determine the roots of nonlinear equations, was separately implemented on each software platform. The process of solving the nonlinear equation through secant iterations was explored and executed independently on both tools. The results of the implementation show that both applications are capable of producing similar root values for the given equation. However, Microsoft Excel offers an advantage in visualizing the iterative process in a detailed and step-by-step manner, allowing users to clearly understand how the solution is derived through each stage of calculation. In contrast, Maple tends to present the final outcome of the iteration process without displaying the detailed steps involved. This study analyzes the strengths and limitations of each application in the context of implementing the secant method for solving nonlinear equations.